2013
DOI: 10.1111/gcb.12109
|View full text |Cite
|
Sign up to set email alerts
|

Food availability outweighs ocean acidification effects in juvenile Mytilus edulis: laboratory and field experiments

Abstract: Ocean acidification is expected to decrease calcification rates of bivalves. Nevertheless, in many coastal areas high pCO 2 variability is encountered already today. Kiel Fjord (Western Baltic Sea) is a brackish (12-20 g kg À1 ) and CO 2 enriched habitat, but the blue mussel Mytilus edulis dominates the benthic community. In a coupled field and laboratory study we examined the annual pCO 2 variability in this habitat and the combined effects of elevated pCO 2 and food availability on juvenile M. edulis growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
367
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 416 publications
(389 citation statements)
references
References 49 publications
17
367
3
2
Order By: Relevance
“…The mechanisms underlying the differential energy response to the stress of ocean acidification between fed and unfed larvae require further study but likely are related to different anabolic (growth) and catabolic (starvation) states. The difference in metabolic response between fed and unfed larvae suggests that nutritional and physiological states impact the response to many environmental stressors, including ocean acidification (47). Such increases in metabolic demand have important implications for long-term resistance to starvation of larval forms with minimal energy reserves (48,49).…”
Section: Feeding State Alters Metabolic Rates Under Acidificationmentioning
confidence: 99%
“…The mechanisms underlying the differential energy response to the stress of ocean acidification between fed and unfed larvae require further study but likely are related to different anabolic (growth) and catabolic (starvation) states. The difference in metabolic response between fed and unfed larvae suggests that nutritional and physiological states impact the response to many environmental stressors, including ocean acidification (47). Such increases in metabolic demand have important implications for long-term resistance to starvation of larval forms with minimal energy reserves (48,49).…”
Section: Feeding State Alters Metabolic Rates Under Acidificationmentioning
confidence: 99%
“…[10]), food availability [11] and predation pressure [12,13], some of which can interact, either counteracting the effects of changing seawater saturation state [11] or exacerbating them [3]. All of these factors probably contribute to how a species modulates calcification internally (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies found that CO 2 -driven acidification had obvious influences on ELS of many marine invertebrates, especially calcified organisms including coral (Doropoulos et al, 2012;Fabricius et al, 2011), coccolithophores (Berry et al, 2002), and mollusk (Kroeker et al, 2013;Thomsen et al, 2013;Waldbusser et al, 2011). OA was predicted to potentially affect individual behaviour such as development, growth, survival, and swimming particularly during the early life stage of marine organisms (Munday et al, 2008).…”
Section: Discussionmentioning
confidence: 99%